An Evaluation of Teaching Stratergies Prescribed by TIM to Teach Science at Grade Eight in Sri Lanka - Karunasena, N.V. (My University, 2011)
Since after the educational reforms implemented in 1972 science is a compulsory subject in Sri Lanka at junior secondary level. The subject is identified as a very important due to its higher educational value. Far most important value is the potential posses in science to develop the rational powers (Lawson, 1995) of students. Thinking abilities related to science process are essential in the intellectual development of the students. The knowledge, skills and attitudes which can bf develop by science is very necessary for all individuals, society and the human kind. During the decades 1960 and 1970 science education in the world was developed by identifying Process Base Science Teaching and Beyond Process Science Teaching. This effort rejected the Product Base Science Teaching. Mere teaching of scientific knowledge is use less when the Process of Science and Influence of Science is neglected. It is very important to evaluate the curriculum of teach science in Sri Lanka. This effort is to evaluate the recommended teaching stratergies of science at grade eight in Sri Lanka by the Teacher Instructional Manuals (TIM). The objectives of the study is to find out the strategies prescribed by the TIM and evaluate them, whether they are suitable for the science teaching with reference to nature of science and the educational values of science. Science instructional manual was peruse with an inventory prepared in which include most recommended teaching stratergies of science and visible strategies recommended in TIM Grade Eight curriculums consist of eight units and 33 sub units/lessons.30 lessons are recommended to teach by using written texts, Out of them they also use dialogs and use poems. Only five instances are there in which observations or testing strategies are used. Therefore it is concluded that the stratergies recommended are not appropriate to teach science